Public Financial Management Reform in the Middle East and North Africa : An Overview of Regional Experience - Individual Country Cases - World Bank (World Bank, 2012)
This report surveys the experience of Middle East and North Africa (MENA) countries on the topic of public financial management reform. Drawing upon a variety of sources, including Public Expenditure and Financial Accountability (PEFA) assessments, country financial accountability assessments, public expenditure reviews, and other documents and reports, and augmented as necessary by interviews with leading reformers, the report seeks to address several major questions. How do MENA countries compare with other comparable countries at similar levels of development with regard to their Public Financial Management (PFM) systems and practices? What has been the substantive content and thrust of PFM reforms in MENA over the last decade? Where have these reforms done well, and where have they struggled? What were the key ingredients for success or failure? And are there lessons in how these reforms were implemented that will be of value to other countries and the donor community?